The academic language proficiency of turkish returnees from germany - (:unkn) unknown (My University, 1995)
The main topic of this article is the language proficiency of the so-called ‘Rückkehrer’ (Turkish returnees from Germany) who were either born in Germany or emigrated to Germany with their parents at a very young age, acquiring Turkish as their first language in the home, and German as their second language in school. Since their remigration to Turkey (generally at the age of 13), they have been attending a special bilingual school programme at a so-called Anadolu lisesi, where some subjects are taught in Turkish, some in German, with English as a third language. The ages of the subjects of this study range from 15 to 17. © 1995 H. Daller.